2016
DOI: 10.1097/qco.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Dos and don’ts for hospital cleaning

Abstract: Purpose of review More evidence is emerging on the role of cleaning and decontamination for reducing hospital-acquired infection. Timely and adequate removal of environmental pathogens leads to measurable clinical benefits for patients. This article considers studies published from 2013 examining hospital decontamination technologies and evidence for cost-effectiveness. Recent findings Novel biocides and cleaning products, antimicrobial coatings, monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 111 publications
1
31
0
1
Order By: Relevance
“…Dancer [106] clearly suggested that more work is required on the AMCs as futuristic antiseptic surfaces.…”
Section: Different Aspects Of Risk-benefit Analysis Of Applicationmentioning
confidence: 99%
“…Dancer [106] clearly suggested that more work is required on the AMCs as futuristic antiseptic surfaces.…”
Section: Different Aspects Of Risk-benefit Analysis Of Applicationmentioning
confidence: 99%
“…44 HPV has also been used in C. difficile and MRSA outbreaks, and may have a role in norovirus infection. 38,46 The addition of UV to standard cleaning reduced VRE rates by 31%. 42 However, both systems are expensive, require trained staff, and are adjuncts to standard physical cleaning.…”
Section: Cleaning Methodsmentioning
confidence: 99%
“…23,36 Patients admitted to rooms previously occupied by VRE or MRSA carriers have a two-to three-fold increased risk of acquisition, and similar rates are seen for A. baumannii, Pseudomonas aeruginosa and, as discussed above, C. difficile. 37,38 Molecular typing of MRO outbreaks has linked the environment, hands of HCW, and patient isolates. HCW may have a primary role in spread, but they can acquire MRO from the environment or inadequately cleaned equipment, including monitors, blood pressure cuffs and tourniquets.…”
Section: Antibiotic Use and Active C Difficile Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel biocides and cleaning products, antimicrobial coatings, auditing practices and automated equipment are widely accessible, but most have not been comprehensively assessed against patient outcome nor subjected to appropriate cost-benefit analyses [37]. It is singularly unhelpful when studies showcasing a new product claim patient benefit but are then found to be confounded by concurrent infection control and/or antimicrobial stewardship initiatives [37].…”
Section: Cleaningmentioning
confidence: 99%